Diagnosis and Treatment of Mucinous Appendiceal Neoplasm Presented as Acute Appendicitis - Ioannis Kehagias; Apollon Zygomalas; Georgios Markopoulos; Thanasis Papandreou; Pantelis Kraniotis (Case Reports in Oncological Medicine)
Appendiceal mucocele is a rare cause of acute abdomen. Mucinous appendiceal neoplasms represent 0.2–0.7% of all appendix specimens. The aim of this study is to report a case of a mucinous appendiceal neoplasm presented as acute appendicitis, discussing the clinical and surgical approach in the emergency setting. A 72-year-old female patient was admitted to the emergency department with a clinical examination indicative of acute abdomen. The patient underwent abdominal computed tomography scan which revealed a cystic lesion in the right iliac fossa measuring 8.3 × 5.2 × 4.1 cm, with calcified walls, and a mean density indicative of high protein content. The patient was taken to the operating room and a right hemicolectomy was performed. The postoperative course was unremarkable. The histopathological examination revealed a low-grade mucinous appendiceal neoplasm with negative regional lymph nodes. Ultrasound and CT are useful in diagnosing appendiceal mucocele and synchronous cancers in the emergency setting. The initial operation should include appendectomy and resection of the appendicular mesenteric fat along with any fluid collection for cytologic examination. During urgent appendectomy it is important to consider every mucocele as malignant in order to avoid iatrogenic perforation causing pseudomyxoma peritonei. Although laparotomy is recommended, the laparoscopic approach is not contraindicated.